Development of Hungarian and German Folk Schools and Primary Teacher's Knowledge in the Course of History (Training and Practice : Journal of Educational Sciences, 2011)
The appearance of professionalisation is one of the basic characteristics of the 19th century development, as a result of which the highly educated, influential intellectual groups developed. The efforts for training primary school teachers emerged in Germany and slightly later in Hungary, and parallel to it the professional groups of primary teachers were formed besides the teachers of higher educational institutions. The demand towards practical knowledge emerged. This knowledge was the basis for the practical knowledge of primary school teachers of folk schools in the second half of the 19th century.